The control and maintenance of desired flow patterns in bends of different orientations. (March 2017) - Zhao, D.; Omar, R.; Abdulkadir, M.; Abdulkareem, L.A.; Azzi, A.; Saidj, F.; Hernandez Perez, V.; Hewakandamby, B.N.; Azzopardi, B.J.
Abstract: Multiphase flows are common in industrial settings and bends in pipe lines cannot be avoided due to space limitations. Gas-liquid two phase flows could form material discontinuities that could have adverse effect on productivity and the pipe network due to sudden variations resulting due to the rapid momentum flux variations at fittings such as bends. Research into gas-liquid flow and bends can be motivated by the effect of the bend on the flow downstream of it which could alter the flow pattern occurring and the performance of downstream equipment. Alternatively, the interest might come from what occurs in the bend itself, there could be dryout of the film on the walls and consequent damage to the heat transfer equipment. Here we present measurements made with a number of accurate and fast responding sensors on three cases, two on the effect of the bend and one considering effects in the bend. The results show that the flow transformations occur in two phase flows depending on the orientation of the bend and the change could be captured using fast sweeping measurement techniques. We present the evidence of effectiveness of several types of measurement techniques that could fit into various combinations of phases. The results, point to how to achieve certain flow patterns. Also recommendations are provided regarding the position of any sensor installed to determine flow pattern. Graphical abstract: Output of tomographic instrumentation showing development of a gas-liquid flow through a pipeline with bends.